An effect of Group motivational interview technique to decrease Thai CV risk in Hypertensive patients and diabetes mellitus typeII - Boonyuen, Teeraporn; Suttipong, Chantawat (Journal of Nakornping Hospital, 2020)
Background: The incidence of cardiovascular disease of the global and Thailand is increasing every year and become a global health concern. Thailand, there are many projects providing the education for diabetes and hypertensive patients, yet the incidence of cardiovascular disease is still rising. Objective: To compare the effect of group motivational interview technique to conventional technique on cardiovascular risk in diabetes and hypertensive patients Method: A quasi-experimental research was conducted to collect pre-test and post-test data through questionnaires and laboratory investigation were collected from database of district health promotion and community center from Java health center information system (JHCIS) in 197 diabetes and hypertensive patients who had Thai CV risk more than 10 then allocate into two groups. The first group was received health education through group motivational interview technique and another group was through conventional technique. Furthermore, the behavior questionnaire was performed at before, 2 and 6 months after receiving health education. The analysis was performed by two tailed t-test to compare the laboratory results, changes between groups and their behavior. Result: The result of this research showed that group motivational interview technique had significantly lower score on Thai CV risk compare to conventional technique (p<0.001). After an experiment, Thai CV risk score was significantly decreased in group motivational interview technique 2.45±4.67 % while in control groups increased by 0.82±5.88 %. Conclusion: Group motivational interview technique can decrease Thai CV risk in patients with hypertension and diabetes mellitus type II.